NITROGEN RUNOFF AND LEACHING LOSSES IN BEEF PRODUCTION SYSTEMS UNDER TWO DIFFERENT STOCKING RATES IN SOUTHERN CHILE PERDIDAS DE NITROGENO POR ARRASTRE Y LIXIVIACION BAJO DOS CARGAS ANIMALES EN SISTEMAS DE PRODUCCION DE CARNE DEL SUR DE CHILE - Marta Alfaro (Universidad de Concepción, 2005)
The Lakes Region of Chile produces 60% of the country's milk and 45% of its meat. Production is expected to increase in the near future, yet there are few data on the environmental impact of local livestock systems. A field experiment was carried out during 2004 to measure nitrogen (N) runoff and leaching losses in beef cattle-grazing production systems near Osorno. Grazing was carried out with Holstein-Friesian steers of 220 kg of initial live weight, with stocking rates of 3.5 and 5 steers ha-1. Water samples were collected during 6.5 months with surface lysimeters and ceramic cups, and were analyzed for nitrate and ammonium. Total losses were calculated as the product of N concentration and accumulated drainage at each sampling date. A significant difference in the total N loss was found between the two treatments (11.1 and 29.9 kg N ha-1, respectively; P < 0.05). The main pathway of N loss was leaching, which contributed 99% of the total N loss. Nitrate was the main form of N loss in runoff (71%) and leaching (99%). Average nitrate concentration in leaching samples was always below the European Community Directive limit. However, nitrate concentration in runoff samples had maximum values of 116 ± 13.8 and 82 ± 22.4 mg L-1 for the 3.5 and 5 steers ha-1 treatments, respectively. For the experimental conditions tested, N losses from beef cattle production systems were low. This was related to the low N inputs in fertilizers used and to the physical and chemical properties of the volcanic soils En la Región de los Lagos de Chile se produce el 60% de la leche y el 45% de la carne del país, esperándose un aumento de la producción en un futuro cercano. Existe escasa información local sobre los impactos ambientales de esta creciente producción agropecuaria. Un experimento de campo fue llevado a cabo durante el 2004 para medir las pérdidas de nitrógeno (N) por lixiviación y arrastre superficial en sistemas de producción de carne de la zona basados en el pastoreo. Para el pastoreo se utilizó terneros Holstein-Friesian de 220 kg de peso vivo inicial, organizados en dos tratamientos con cargas de 3,5 y 5 terneros ha-1. Las muestras de agua fueron colectadas durante 6,5 meses con lisímetros superficiales y cápsulas cerámicas, y analizadas para nitrato y amonio. Las pérdidas totales de N fueron calculadas como el producto de la concentración de N en las muestras y la cantidad de drenaje disponible, para cada fecha de muestreo. Se observó diferencias significativas en las pérdidas totales de N entre los dos tratamientos (11,1 y 29,9 kg N ha-1, respectivamente; P=0.05). La principal vía de pérdida de N fue la lixiviación, la cual contribuyó con un 99% del total de N perdido (P=0.05). El nitrato fue la principal forma para la pérdida de N por arrastre (71%) y lixiviación (99%). La concentración promedio de nitrato en los lixiviados estuvo siempre bajo el límite de la Directiva de la Unión Europea. Sin embargo, la concentración de nitrato en muestras de arrastre tuvo un máximo de 116 ± 13.8 y 82 ± 22.4 mg L-1 para los tratamientos de 3.5 y 5 terneros ha-, respectivamente. Bajo las condiciones experimentales estudiadas, las pérdidas de N desde sistemas de producción de carne fueron bajas. Esto fue relacionado con la baja cantidad de N aplicado como fertilizantes, y las propiedades físicas y químicas de suelos volcánicos